(untitled) (American Journal of IR 4.0 and Beyond, 2023)
In perfect, ideal situations, everything is running smoothly and under the best conditions. The business is running smoothly, all the customers are satisfied and all the products delivered are in order. Suddenly, at any time, unexpected problems arise and affect the smooth running of the business. If zero failures are therefore unthinkable in any unstable environment subject to uncertainty, what can we say about the link between failure and resilience? Indeed, despite the concrete truth of the environment, it is in the latter that many beautiful things arise. Willingness versus action is the source of resilience and progress. This paper presents an overview of the theoretical framework linking context failure, compensatory strategies and resilience. More specifically, we focus on the contribution of compensatory or restitution strategies to the recovery of resilience. From the literature review, we examined several research works on failure contexts in order to subsequently propose a research model reflecting the role of compensations in recovery and resilience.